Peningkatan Literasi Bagi Anak Tingkat TK dan SD di TPA Miftahul Jannah di Dusun Kaliadem - Pratama, Dhimas Aditya; Arizza, Muhammad Zayyan; Wafaqihah, Falikhatus; Nurwindra, Argya Daniswara; Diyanah, Salma; Amal, Fachri Ikhlaslul; Asri, Setia Wulan; Arnianti, Tarisa Nur Eka; Sari, Ajeng Puspo; Fashola, Alfitra Salma; Humaini, Arif (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The Community Service Program (Pengabdian Masyarakat) aims to help the community enhance their learning spirit and improve the quality of Islamic religious education by teaching at TPA Miftahul Jannah. The problem faced is that children quickly get bored with monotonous learning. This program is designed to encourage children and teachers to rekindle their enthusiasm for studying the Quran. This activity focuses on strengthening the understanding of the Qur'an, daily prayers, and noble character through interactive and enjoyable learning methods. The methods used in this program include participatory approaches and active learning to enhance children's understanding, such as audiovisual media, discussions, and question-and-answer sessions. In addition, a learning evaluation was conducted to measure the students' understanding of the material taught. Of the 31 children involved, 80% experienced an improvement in their ability to read Iqra and the Qur'an, with the reading fluency rate increasing from 40% before the activities to 80% afterward. In the short surah memorization program, out of a total of 16 children who participated in this program, 37.5% successfully memorized well, although 62.5% of the others still experienced difficulties, which were influenced by the children's level of focus during the learning process. The activity of watching educational films was attended by all the children, and 90% of them were able to answer questions correctly during the Q&A session, demonstrating a good understanding of the material. Success indicators include improved reading skills, children's enthusiasm, and understanding of Islamic values, with 70% of parents attending the activities and supporting their children. Based on qualitative evaluation conducted through observation, it was found that this program successfully increased children's enthusiasm for learning